Placental pathology in COVID-19 affected pregnant women: A prospective case-control study. (July 2021) - Tasca, Chiara; Rossi, Roberta Simona; Corti, Silvia; Anelli, Gaia Maria; Savasi, Valeria; Brunetti, Federica; Cardellicchio, Manuela; Caselli, Emilio; Tonello, Cristina; Vergani, Patrizia; Nebuloni, Manuela; Cetin, Irene
Abstract: Introduction: During pregnancy, SARS-CoV-2 infection may cause an abnormal development of the placenta, thus influencing maternal and fetal outcomes. Few studies have reported data on placental morphology and histology in infected pregnant patients, although not compared with carefully matched controls. The aim of this study is to compare placental morphology and histology of pregnant women affected by SARS-CoV-2 to non-infected controls. Methods: This is a prospective multicenter case-control study on 64 pregnant women affected by SARS-CoV-2 who delivered at term or late-preterm. Data were collected about pregnancy course, maternal and fetal outcomes, placental biometry and macro- and microscopical morphology. 64 not-infected women were identified as controls, matched by age, body mass index and ethnicity. Results: Cases and controls had similar fetal and maternal outcomes. No significant differences were observed in placental macro- or microscopical morphology between the two groups. In the cases treated with antivirals, chloroquine, LMWH or antibiotics, placentas were heavier but not more efficient than the non-treated, since the fetal/placental weight ratio did not differ. Moreover, delayed villous maturation was more frequent in treated women, although not significantly. The newborns whose mothers received oxygen therapy as treatment had higher levels of umbilical cord pO₂ at birth. Discussion: In this prospective case-control study, SARS-CoV-2 infection during the third trimester did not influence placental histological pattern. Pharmacological and oxygen therapy administered to women affected by this viral infection could impact maternal and fetal outcomes and be associated to placental histological alterations. Highlights: CoViD during the third trimester did not influence placental histological pattern. Drugs used for treatment of CoViD-19 made placentas heavier but not more efficient. Delayed villous maturation was more frequent in treated women. Umbilical cord pO₂ at birth was higher when mothers received oxygen therapy.